Have people ‘had enough of experts’? The impact of populism and pandemic misinformation on institutional trust in comparative perspective - Štětka, Václav; Brandao, Francisco; Mihelj, Sabina; Tóth, Fanni; Hallin, Daniel; Rothberg, Danilo [UNESP]; Ferracioli, Paulo [UNESP]; Klimkiewicz, Beata (Taylor & Francis, 2024)
Public trust in institutions is a key prerequisite for effective crisis management. However, the rise of populism and misinformation in recent years made it increasingly difficult to maintain institutional trust. Despite this recognition, we still lack a systematic understanding of how exposure to misinformation and populist political orientation affect people’s trust in institutions. This paper fills this gap by adopting an original approach to trust, focusing on prospective trust rather than trust in the present, and by comparing four countries led by populist leaders during the pandemic–Brazil, Poland, Serbia, and the United States. The comparative design allows us to consider not only the role of individual-level factors (populist attitudes and misinformation exposure) but also the role of different approaches to the COVID-19 pandemic adopted in the four countries. The study utilizes data from a cross-sectional survey, carried out between November and December 2022 (N = 5000). Our findings show that populist attitudes are the most significant predictor of distrust in political institutions in all four countries. Believing in false information related to COVID-19, on the other hand, has a stronger impact on distrust in expert institutions–public health authorities, scientists, and medical professionals. The data also highlight the importance of local context and different approaches to handling the pandemic in the dynamics of trust. In Poland and Serbia, populist voters have more trust in both healthcare authorities as well as in political institutions; however, in Brazil and the United States, populist voters were more likely to distrust expert institutions.
Keywords: COVID-19; misinformation; pandemic; populism; Trust